(3cJGH aj GdMceIs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO adeG cGfJ GdMceI CWjH eG jLJfi CMHHJ Cf CLeY efgG jchf cGdCfehPL dNGWHgG s
(3BNQgG (B:s
(3hjZJGH EPG ZGH hjTeJ HGdeUjHI MO GdMde JQc GdEfJbGe eY EecGf GdbOQI hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3fSNI NRGFfjI HQSe ehdGfG GdSdWGf GdfGUQ CHj GdSYGOGJ eMeO YR fUQghGdeNWhW jTJed Ydi EKfi YTQ aUdkGs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs